Assessment of micro-climate in Chinese solar greenhouse equipped with a Pad-Fan Cooling system by different turbulence models - Wenhe Liu; Yunshu Liu; Feng Zhang; Zhanyang Xu; Haonan Sun; Wei Yu; Mengmeng Yang (Smart Agricultural Technology)
This paper was combined four turbulence models (SST Model, Stke Model, Rngke Model, Rke Model) with the Discrete Ordinates radiation model to simulate the variations of temperature, humidity, and wind speed in an Chinese solar greenhouse equipped with a Pad-Fan Cooling system. The numerical simulation result were verified by measurement data under same condition to evaluate the accuracy of the four turbulence models. The results showed that the temperature, humidity, and wind speed were more accuracy predicting by SST Model. The maximum relative errors between the simulated and measured results for temperature, humidity, and wind speed were 15.47 %, 16.55 %, and 20.16 %, respectively. The minimum relative errors of temperature, humidity, and wind speed were 0.00007 %, 0.0340 %, and 0.0260 %, respectively. The linear fit degree R2 of SST Model was the highest, which is 0.9735, 0.8466, 0.9956. The lowest root mean square error RMSE of SST Model for temperature, humidity, and wind speed was 0.6247 °C, 2.5098 %, 0.0524 m/s. Therefore, the SST Model was most accurately model rather than Stke Model, Rngke Model, Rke Model on predicting the temperature, humidity, and gas flow environment in a Chinese solar greenhouse equipped with a Pad-Fan Cooling system.